Relationship of Blood Groups (ABO & Rhesus) and Breast Cancer in Bangladesh - Khan, Ghulam Mostafa; Rahmatullah, Md; Mostafa, Ishita (Journal of Enam Medical College, 2014)
Correction: On the website, on 16/08/2014, the first author was changed from Chulam Mostafa Khan TO Ghulam Mostafa Khan. The PDF was correct. Background: The association of blood groups with breast cancer in our country is not fully established elaborately and large scale studies have not been carried out till now. Therefore this study was designed to find out the possible relationship of different blood groups with breast cancer. Objective: To determine the relationship of various types of breast cancer with ABO and Rh blood groups among the female patients of our people. Materials and Methods: This cross sectional study was conducted in the cancer unit of Delta Medical College and Hospital, Dhaka from January 2011 to February 2013. After proper and ethical consideration total 112 female patients with breast cancer were included in this study. Various factors like age, family history, metastasis, type of cancer were considered in this study. The blood groups of the patients were done by standard ABO and Rh typing methods (Forward & Reverse grouping by test tube method). Results: Among 112 breast cancer patients of our country, ductal breast cancer was found in 108 (96.42%) subjects, distant metastasis was found in 93 (86.9%) cases and positive family history in 70 (62.50%) subjects. Conclusion: Ductal type of breast cancer with positive family history and distant metastasis is common in different blood groups in our country. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19679 J Enam Med Col 2014; 4(2): 106-109